Kult świętych w piśmie Hieronima „Przeciw Wigilancjuszowi”. Kwestia współczesnych tłumaczeń - Nocoń, Arkadiusz (Vox Patrum, 2020)
One of the controversies between Catholicism and Protestantism is the problem of the mutual influence of the community of saints in heaven and the pilgrimaging people on earth. As is known, Protestantism has greatly reduced the impact of the community of saints on the faithful on earth, profiting undoubtedly from the heritage of one of the precursors of Protestant thought – Vigilantius. It is a fact that most of the views of this Gallic priest on the veneration of the saints are binding today in Protestant ecclesial communities. As we are celebrating the 1600th anniversary of the death of St. Jerome, it seems appropriate to recall his reaction to the views held by Vigiliantius. St. Jerome’s teaching expressed in the little work Adversus Vigilantium not only blocked the expansion of the doctrine of this Gallic priest, but also entered to a large extent into the official teaching of the Church and the liturgy. Unfortunately, this work of St. Jerome has not had many translations into modern languages and most of the existing versions are based on the text taken from the Patrologia Latina, which complicates the understanding of the most original thought of St. Jerome on the communion of the saints and on relics. The Adversus Vigilantium explains that the “communion” of the saints with the living is more intensive in the burial places of the saints, and so, adjacent to their relics. In his short treatise, St. Jerome does not specify the character of this intensive presence. He only writes that it manifests itself in “signs and miracles” done by the saints and in their powerful impact on evil spirits.